CSF neurofilament proteins in the differential diagnosis of dementia. Issue 9 (21st February 2007) - de Jong, D; Jansen, R W M M; Pijnenburg, Y A L; van Geel, W J A; Borm, G F; Kremer, H P H; Verbeek, M M
Abstract : Background: Neurofilament (NF) proteins are major cytoskeletal constituents of neurons. Increased CSF NF levels may reflect neuronal degeneration. Objective: To investigate the diagnostic value of CSF NF analysis to discriminate in relatively young dementia patients between frontotemporal lobe degeneration (FTLD) and early onset Alzheimer's disease (EAD; onset ⩽65 years of age), and in elderly dementia patients between dementia with Lewy bodies (DLB) and late onset AD (LAD; onset >65 years of age). Methods: In CSF of 28 FTLD, 37 EAD, 18 DLB and 33 LAD patients, and 26 control subjects, we analysed NF light chain (NFL), phosphorylated NF heavy chain (pNFH), amyloid β42 protein (Aβ42 ), total tau and tau phosphorylated at threonine 181 (p-tau181 ). Results: CSF NFL levels were higher in FTLD patients compared with EAD patients (p<0.001), and diagnostic accuracy of p-tau181 and Aβ42 analysis improved with addition of NFL analysis (sensitivity 86%, specificity 100%). CSF pNFH levels were elevated in DLB, LAD and FTLD compared with controls (p<0.05) but no significant differences were found between the dementia groups. Conclusions: In the diagnostic workup of relatively young dementia patients, CSF NFL levels may play a role in the discrimination between FTLD and EAD, especially in combination with Aβ42 and p-tau181 analysis.